DIAGNOSIS OF LIVER ABSCESS BY ULTRASOUND - Idrees, Mohammad; Ilyas, Mohammad (Journal of Ayub Medical College Abbottabad, 1996)
Amoebic liver abscess is common in Pakistan whereas pyogenic abscess is more prevalent in the west. Timely diagnosis of the liver abscess significantly lowers the morbidity and mortality. Present study involves ultrasound examination of 200 consecutive patients in a five-year period (September 1990 - August 1995) at civil teaching hospital, Abbottabad and private clinics. One hundred and ninety-six patients (98%) had amoebic liver abscess. In a similar number of cases the abscess was solitary. Abscess was located in right hepatic lobe in 184 (92%). Majority of patients (76%) were males while 24% were females. Age of our patients was between 10-60 years and size of the lesion varied between 3-16 cm. Ultrasound has proved to be excellent imaging modality in the diagnosis liver abscess. In selected cases abscess can be aspirated or drained under ultrasound guidance.